Konflik Internal Dan Rekrutmen Politik Partai Golkar Sulawesi Barat (Studi Kasus: Konflik Internal dan Keterpilihan Kader dalam Menghadapi Pemilu dan Pilkada di Sulawesi Barat 2014) - Asmadianto, Asmadianto; Nurmandi, Achmad (Universitas Muhammadiyah Yogyakarta, 2015)
Conflicts on political parties is a routine phenomenon that occurred in Indonesia. This happens due to lack of awarenessin organizing both the elite and party leaders in reducing conflict.Meanwhile, the Golkar Party is the party whoplaced second in the 2014 election yesterday, but Golkar did not choose/decide a candidate to be a President. Suchconditions are the initial emergebce of internal conflict in the Golkar party DPD West Sulawesi, where there is a viewdifference of cadres in the district against the direction of the coalition that was built under the leadership of the DPPhandled by Aburizal Bakri. That difference led to the dismissal of Anwar Adnan Saleh, chairman of DPD Golkar Party ofWest Sulawesi.Based on the explanation above, while the issues raised in this study is:first, how far is the extent of theinternal conflicts within the Golkar DPD of West Sulawesi, second, how is the relations of conflict with the election ofcadres on the nomination of the head of the region in several districts in West Sulawesi.Meanwhile, the method usedin this research is qualitative descriptive with the use of case studies (case studies) that intensively conducted,thorough and in-depth on aorganization, institution or certain symptoms. While data collection techniques that wasused are observation: to observe the objective conditions in the field, interviewing actors involved in the internalconflict DPD Golkar Party and Documentation.The results showed that: first, the cause of the conflict is a result of thedeactivation of DPD Golkar chairman by the board of DPP that involving protests by a number of cadres in the areaover the dismissal. Secondly, the presence of Nurdin Halid as a Tasks Executor increasingly heat uo the embryo ofInternal conflicts in the party. Third, as a result of doing the dismissal by the board DPP to Anwar make part of otherDPD to highlight and heat uop the conflict because they think that the central committee does not consider the resultof the dismissal, fourth, a split that occurred in the internal of Golkar Sulbar greatly affect the electability of cadres inthe nomination due to conflict rushing in Golkar, thus forcing the heads of district administrators do the election offigure to win the elections. Not even a half-hearted to enforce Golkar to form a coalition with the bearer party of acandidate in one district in West Sulawesi.